Removal of mercury(II) through adsorption on titania nanofibers - Dixit A.; Atal K.; Mishra P.K.; Alam M.S. (My University, 2025)
Titania nanofibers were synthesized using a combination of sol-gel and electro-spinning techniques followed by calcination to eliminate organic phase. Effects of precursor and polymer concentration and temperature on fiber morphology were studied. The BET adsorption, FTIR spectroscopy, SEM and XPS techniques were used to characterize titania nanofibers. The obtained fibers were properly aligned and smooth. Presence of titanium(IV) and Ti-O bonds were confirmed. The fibers exhibited a large surface area (740.2 m2/g) and high uptake efficiency (95.5 %) for mercury(II). Adsorption equilibrium obeyed Freundlich isotherm and process followed pseudo second order kinetics.